(untitled) (diségno, 2022)
The concept of archive is customarily associated with the systematic collection of documents to be kept as a testimony of writings or graphic elaborations that permit subsequent consultations. Archival materials generally refer to episodes related to a recent or ancient past that assumes historical documentary values to be safeguarded for the benefit of future research. Going beyond the rhetorical and outdated notion of a dusty space used for storage, archives with the aid of digitalization have transcended the physical limits of on-site consultation; it is, however, necessary to consider the further exploratory potentials concerning the research and communication of contents related to the materials deposited in them and, specifically, architectural drawings. [read more]